Analisis Korelasi Desain Karakter Video Game dan Loyalitas Video Game Pada MMO Studi Multi-method - Jimmy Pratama; Kendy Junianto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
RPG is a game genre where a player can play a role in the game. RPG genre games have various genres, one of which is MMO which offers players to interact with many players at the same time. The Indonesian game industry does not yet have a role in competing with foreign products. Therefore, the purpose of this research is to examine character design. which can affect one's interest in playing. The method used in this study is a multi-method, namely a mixture of quantitative and qualitative. Quantitative used is distributing questionnaires and qualitatively collecting data by interview. The results of the quantitative study showed that the appearance of the facial features and good looks of a character influenced the player's interest in playing, while the qualitative results were not significant in terms of the appearance of the facial features and good looks of a character.